Baroreflex Activation Therapy (BAT) Effectiveness Among Heart Failure Patients: A Systematic Review and Meta-Analysis - Farahdina Farahdina; Muhammad Ilham Hernawan; Wiryantari Akhdani Pratiwi; Hapsary Puteri Widodo; Vatine Adila (Eduvest - Journal of Universal Studies, 2021)
Heart failure is promoted by the imbalance of sympathovagal, which increased sympathetic and decreased parasympathetic activity. BAT, an electrical stimulation technology, cause the baroreflex to be activated and balances the sympathovagal. Systematic review and meta-analysis were conducted, including published reports about the effectiveness of BAT in heart failure patients from PubMed, Embase, Cochrane, and Google Scholar to calculate the pooled standard mean difference and 95% confidence interval (95% CI) using either random or fixed effect model. Our search strategy identified 161 possible studies. Thirteen studies have been included as a full-text review. We excluded seven of these papers due to review, and our analysis has included six papers. Our combined analysis has shown that BAT is associated with an improvement in NYHA class compared to control (0.19[95%CI: 0.11-0.31], p = 0.000). Our pooled analysis also found that BAT, compared to control, was associated with 6-MHWD improvement, (-136.25[95%CI: -181.34 - -91.17], p = 0.000). Our pooled analysis also found that BAT, compared to control, was associated with HF hospitalization (-6.38[95%CI: -8.46 - -4.30], p = 0.000). BAT has a significant effect on improving NYHA Class, 6-minute hall walk distance, and decreasing HF patient's hospitalization days. Meanwhile, there is an insignificancy on LVEF and QoL improvement in HF patients. Future studies are still needed.